Effect of probiotic Lactobacillus on lipid profile: A systematic review and meta-analysis of randomized, controlled trials. - Yucheng Wu; Qingqing Zhang; Yin Ren; Zhongbao Ruan (PLoS ONE)
Objective To assess the efficacy of probiotic Lactobacillus on serum lipids using a meta-analysis of randomized, controlled trials. Methods Fifteen studies containing 15 trials, with 976 subjects were included. The pooled WMD was calculated by random effects model. Results Probiotic Lactobacillus consumption significantly reduced TC by 0.26mmol/l (95% CI, -0.40 to -0.12) and LDL-C by 0.23mmol/l (95% CI, -0.36 to -0.10). Subgroup analysis of trials found significantly reduction of TC using L. plantarum and reduction of LDL-C using L. plantarum or L. reuteri. No significant effects were found on TG and HDL-C levels after supplementation with probiotic Lactobacillus. While, subgroup analysis found significantly beneficial effects on TG and HDL-C by consuming synbiotic food, containing L. sporogenes and inulin. Conclusion Consuming probiotic Lactobacillus, especially L. reuteri and L. plantarm, could reduce TC and LDL-C significantly. The study also suggested significantly beneficial effects on TG and HDL-C by consuming synbiotic food, containing L. sporogenes and inulin.